Composition–rheology relationships in alkali–silica reaction gels and the impact on the gel's deleterious behavior. (May 2016) - Gholizadeh Vayghan, Asghar; Rajabipour, Farshad; Rosenberger, James L.
Abstract: Alkali–silica reaction (ASR) continues to be a major challenge to the durability of concrete structures. This is in part because the relationships between the composition, properties, and behavior of ASR gels in concrete are poorly understood. Gels with high pore solution pH, osmotic pressure, and rheological (e.g., yield stress) and swelling properties are the most deleterious. In this paper, the effects of the composition (primarily Ca/Si and Na/Si) of synthetic ASR gels on these characteristics are investigated, and regression analyses are done on the data. The pessimum combination of osmotic and rheological properties was found in the case of gels having intermediate calcium and high sodium contents (i.e., Ca/Si = 0.2 and Na/Si ≈ 0.85), leading to the highest estimated swelling pressures. These gels also developed the most alkaline pore solutions. While highest yield stresses were observed in the gels with low calcium and low sodium, they showed negligible osmotic and swelling pressures.